Pengaruh Akuntabilitas, Transparansi, dan Kompetensi Aparatur Desa Terhadap Efektivitas Pengelolaan Dana Desa di Kecamatan Sungai Apit (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of accountability, transparency, and competence of village officials on the effectiveness of village fund management in Sungai Apit District. The study uses a quantitative approach with primary data collected through questionnaires distributed to village officials. The study population includes all village officials in Sungai Apit District, while a sample of 42 respondents was determined using a purposive sampling technique, namely village officials directly involved in village fund management. Data were analyzed using multiple linear regression because the study aims to test the influence of several independent variables simultaneously or partially on one dependent variable. The results of the study indicate that simultaneously, accountability, transparency, and competence of village officials have a significant effect on the effectiveness of village fund management. Partially, accountability and transparency have a positive and significant effect, while the competence of village officials does not have a significant effect on the effectiveness of village fund management. These findings indicate that strengthening accountability and transparency is a major factor in increasing the effectiveness of village fund management in Sungai Apit District.